PEMBUATAN BAHAN AJAR BERMUATAN KECERDASAN KOMPREHENSIF MATERI KALOR DAN ALAT OPTIK UNTUK PEMBELAJARAN SISWA KELAS X SMA - Suciani Liniswanti; Asrizal Asrizal; Zulhendri Kamus (Universitas Negeri Padang, 2015)
The human resources of Indonesia was expected having knowledge and character through the 2013 curriculum. The goal of this research were to determine validity, description, practicality, and effectiveness of the use of comprehensive teaching materials for senior high school. Kind of research was Research and Development (R & D). This study design limited testing before and after the treatment given. The object of research was a charged with comprehensive learning materials. The data collection instruments used in the form of validation sheet, test sheet practicality, effectiveness test sheet achievement test, the observation sheet spiritual values, social values observation sheets, and student skill assessment sheets. Analysis techniques of product and data were validity, practicality, effectiveness of product. Based on data analysis that has been done to that instructional materials have high validity with a value of 88,71. There were results of this research. First, design appropriate instructional materials have a structure that was a good teaching materials. Second, value practicality of teaching materials by teachers and students were 88,90 and 82,47. Charged with comprehensive learning material effectively used to develop a comprehensive intelligence of students